MEMAKNAI FENOMENA KETERLAMBATAN PENGELUARAN KAS DAERAH PADA SEKRETARIAT DAERAH KABUPATEN GIANYAR - Mahendra, I Wayan Budi; Sudana, I Putu; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017, 2017)
This study aims to find out how the concerned parties understand and interpret such phenomenon. In order to explore the understanding of related parties, phenomenology is used as a methodology, with interpretive paradigm as a study umbrella. The focus of the study taking place at the Regional Secretariat of Gianyar regency of three informants who deal directly with the Regional Accounts Payable process. Qualitative data were collected by conducting in-depth interviews and participant observation. The findings indicate that the leadership has an important role in the process of local cash outlay. The key problem faced is the quality of leadership that ultimately affeects the non-optimal financial planning, competence apparatus and bureaucratic. This study advises that it is required some efforts such as: arranging financial management training, regular meetings to evaluate the performance and implementing shorten bureaucracy policy.